ロケット ニヨル オーロラ・ヒス ノ カンソク - 鎌田, 哲夫; カマダ, テツオ; KAMADA, Tetsuo (国立極地研究所, 1975)
P(論文) S-210JAロケット2機によるVLF hissの観測が行われ,1機はオーロラ・アークの出現時,もう1機は,オーロラは出現していないが,地上観測で12kHz帯VLF hissが観測されている時期に打ち上げられた.両機とも,高度95～110kmの領域で.VLF帯の電磁波現象が強くなるのが観測された. Two rockets with VLF receivers were launched from Syowa Station in Antarctica to study the electro-magnetic properties of auroral arcs. This paper is a preliminary report on the rocket observations. One payload was launched during relatively quiet auroral arc conditions. The other payload was launched while a 12 kHz VLF hiss recorder at a ground station showed fairly strong hiss, but no auroral arc was observed. In both cases, the electric field intensity in the VLF range was observed to increase at an altitude from 95 to 110km. departmental bulletin paper